LEGAL AND POLITICAL CHARACTER OF LEGISLATIVE AND EXECUTIVE POWER RELATIONS IN THEORY AND PRACTICE - Cerovic, Drazen (European Scientific Journal, ESJ, 2013)
One of the main features of modern legal political systems is a joint decision-making of legislative and executive authorities. As a rule, the constitution of a specific country formally determines its relations. The system of mutual control and restrictions between the different branches of state powers, in theory, is known as checks and balances, to a greater or lesser extent is present in most countries of the democratic political and legal structure. Parliamentary control of the executive power is a relatively "new" discipline19 in transition countries. In this sense, the work on its development and improvement, represents an issue of special priorities and moreover a condition sine qua non of ensuring legitimate and democratic form of government in every state. Parliamentary control is the key to democracy, because Parliament by the nature of his constitutional legal position can substantially influence the actions of government. Countries in transition represent, tentatively, new systems with many challenges in the future. They are in the period of constitution of democratic political and legal system, as well as creating of a quality model of parliamentary control of the executive power within it.